2009
DOI: 10.1002/pits.20434
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between treatment integrity and acceptability of reading interventions for children with Attention‐Deficit/Hyperactivity Disorder

Abstract: This study examined the relationship between treatment integrity and acceptability for reading interventions across two consultation models, intensive data-based academic intervention (IDAI) and traditional data-based academic intervention (TDAI). Participants included 83 first-through fourth-grade students who met research criteria for Attention-Deficit/Hyperactivity Disorder and evidenced academic difficulties and their general and/or special education teachers. Reading interventions were developed through i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
37
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 45 publications
3
37
0
Order By: Relevance
“…Given the links between program acceptability, engagement, and efficacy (Cowan and Sheridan 2003;Mautone et al 2009), establishing the acceptability of school-based mindfulness programs from the perspective of the child adds substantially to the literature. The results of the current study provide useful and important evidence for the value of obtaining acceptability information from children involved in the TRIPLE R mindfulness program.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Given the links between program acceptability, engagement, and efficacy (Cowan and Sheridan 2003;Mautone et al 2009), establishing the acceptability of school-based mindfulness programs from the perspective of the child adds substantially to the literature. The results of the current study provide useful and important evidence for the value of obtaining acceptability information from children involved in the TRIPLE R mindfulness program.…”
Section: Discussionmentioning
confidence: 99%
“…Kazdin (1980) defined treatment acceptability as the extent to which those non-professionals involved in a treatment judge it to be fair, reasonable, appropriate and non-intrusive. Research has demonstrated links between treatment acceptability, ratings, and the efficacy of the treatment to the extent that the acceptability of treatment can actually contribute to its efficacy (Cowan and Sheridan 2003;Mautone et al 2009). This finding highlights the inherent value of acceptability data to an overall program evaluation.…”
Section: Program Evaluation and Acceptabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…By contrast, consultee-centered consultants plan research-based interventions together with consultees, asking about perceived intervention acceptability and adjusting accordingly, rather than telling consultees which intervention is most appropriate to implement without seeking consultee feedback. Some research has demonstrated a linkage between treatment (intervention) acceptability and treatment (intervention) adherence/fidelity (e.g., Allinder & Oates, 1997;Dart, Cook, Collins, Gresham, & Chenier, 2012;Mautone et al, 2009), which may be facilitated by consultees' perceived ownership of the problem and solution.…”
Section: Problems and Solutions Are Ultimately Owned By Consulteesmentioning
confidence: 98%
“…Researchers examining academic interventions have described several factors that may impact instructional implementation, including the complexity of the strategy, the teacher's understanding of the strategy, the teacher's ability to implement given his or her current resources (such as degree and training), and the teacher's perception of the value and feasibility of implementation (Chafouleas, Briesch, Riley-Tillman, & McCoach, 2009;Mautone et al, 2009). Success of implementation is believed to be determined by the interplay of these varying factors instead of one single underlying dimension (Orne and Binik, 1989).…”
Section: Introductionmentioning
confidence: 98%